Pressure-Less Liquid-Phase Sintering of Aluminum-Based Materials - Ana Teresa Sucgang; Laurent Cuzacq; Jean-Louis Bobet; Yongfeng Lu; Jean-François Silvain (Journal of Manufacturing and Materials Processing)
Rapid technological advancements and the growing focus on sustainable practices have significantly expanded the potential applications of aluminum (Al) and its alloys, leading to a steady increase in demand over the years. This study investigated the densification of Al and Al-based materials using pressure-less liquid-phase sintering. Samples with 4–20 vol.% AlSi12 sintered at 640 °C for 1 h achieved the highest relative density (RD) and the lowest global porosity (GP) without exhibiting any shape deformation. In general, increasing the amount of sintering aid improves the density of the samples. This was confirmed by microstructural analysis using SEM, which revealed the progression of density—from initial particle coalescence at 4 vol.% AlSi12 to the development of microstructures with filled pores and well-defined grain boundaries at 20 vol.% AlSi12. X-ray diffraction (XRD) analysis also revealed an expanded lattice parameter, with minimal microstrain and a crystallite size closely resembling those of the initial Al powder. Samples with a relative density greater than 90% demonstrated thermal conductivities ranging from 170 to 200 W/mK and an average hardness of 29 HV5. Densification was further enhanced by increasing the compaction pressure from 50 MPa to 100–200 MPa for samples containing 12–20 vol.% AlSi12. The Al-based material compacted at 200 MPa and with 15 vol.% AlSi12 achieved the highest RD of approximately 99%. It exhibited a thermal conductivity of 195 W/mK at 30 °C and 190 W/mK at 70 °C, along with a hardness of 30 HV5.